Islamic-Based Neuroparenting, Emotional Intelligence, and Character Development in Indonesian Muslim Diaspora Early Childhood in Australia: A Sequential Explanatory Mixed-Methods Study - Ulfah, Maulidya; Suci Rohmadheny, Prima; Diah Andika Sari (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study develops and tests an Islamic-based neuroparenting framework to strengthen emotional intelligence and character formation among Indonesian Muslim diaspora children (4 to 6 years) in Australia.Design/methods/approach – A sequential explanatory mixed-method design was used. Survey data from 150 Indonesian diaspora parents across three Australian regions were analysed with SEM-PLS. Measures assessed Islamic-based neuroparenting, children’s emotional intelligence, and character development. Follow-up semi-structured interviews with 15 parents were analysed thematically to explain the statistical patterns.Findings – Mean scores were high for neuroparenting (M = 4.30), emotional intelligence (M = 4.18), and character development (M = 4.26). Islamic-based neuroparenting predicted emotional intelligence (β = 0.58, p < 0.001) and character development (β = 0.52, p < 0.001). Emotional intelligence predicted character development (β = 0.47, p < 0.001). Explanatory power was moderate to strong (R2 = 0.34 for emotional intelligence; R2 = 0.49 for character). Interviews highlighted parental self-regulation, affective closeness, and daily Islamic routines as mechanisms supporting children’s calming, empathy, and prosocial behaviour.Research implications/limitations – The study provides empirical evidence for integrating Islamic values and neuroscience in parenting models, though its generalizability is limited to Indonesian diaspora families in Australia. Future research may extend this work by comparing diaspora communities across different cultural settings or by examining longitudinal outcomes.Practical implications – The model can guide parents, early childhood educators, Muslim schools, and community organisations in designing parenting support that prioritises emotional responsiveness, developmentally appropriate stimulation, and consistent value transmission across home and school contexts.Originality/value – The study operationalises an integrative diaspora parenting model that synthesises neurodevelopmental principles with Islamic moral and spiritual values, supported by mixed-method evidence.Paper type Research paper